(untitled) (Yearbook - Faculty of Economics, 2018)
From the pleiad financial innovation known in the financial systems some of course belong to the new financial instruments, used by banking institutions. Liberalization that followed the financial markets allow a range of innovations that are analyzed in this paper. The aim of this paper is to show the existing instruments and their variants, as well as the existence of new products that make up the spectrum of tools that for banks institutions. This paper is a theoretical review of the material.